Usage of the wearable cardioverter-defibrillator during pregnancy. (August 2022) - Olic, J.-Jacqueline; Stöllberger, Claudia; Schukro, Christoph; Odening, Katja E.; Reuschel, Edith; Fischer, Marcus; Veltmann, Christian; Duncker, David; Baessler, Andrea
Abstract: Background: Pregnancy can trigger or aggravate the risk for life-threating arrhythmias in cardiac diseases. Pregnancy is associated with reluctance for implantable cardioverter-defibrillators (ICD) due to concerns about radiation. Thus, the wearable cardioverter-defibrillator (WCD) might be an option during pregnancy. Aim of the study was to collect experiences about the use of WCD in pregnancy. Methods and results: This study retrospectively included eight women who received a WCD during pregnancy. They suffered from ventricular tachycardia (VT) without known cardiac disease (n = 3), Brugada syndrome (n = 1), hypertrophic cardiomyopathy (n = 1), dilated cardiomyopathy (n = 1), non-compaction (n = 1), and survived sudden cardiac arrest during a preceding pregnancy (n = 1). WCD usage was started between 13 and 28 weeks of gestation. WCD wearing period ranged from 3 days to 30.9 weeks, WCD wearing time ranged from 13.0 to 23.7 h per day. Two women (25%) abandoned WCD already during pregnancy. Neither appropriate nor inappropriate WCD shocks were recorded. Antiarrhythmic management included beta-blockers (n = 5) and flecainide (n = 2). After delivery, ICD were implanted (n = 4), refused (n = 2) and estimated not necessary after successful catheter ablation (n = 2). Conclusion: Uneventful pregnancy is possible in women at risk for sudden cardiac death by interdisciplinary monitoring and diligent pharmacotherapy protected by the WCD. Since no WCD shocks were recorded, the effectiveness of WCD during pregnancy is still unclear. However, arrhythmia detection by WCD was very good despite the changed anatomy in pregnancy. Nevertheless, further studies are necessary to assess effectiveness of WCD in pregnant women. Furthermore, efforts should be made to increase the wearing adherence of WCD during pregnancy.